Euthanasia Dalam Perspektif Hukum Pidana Yang Berlaku Di Indonesia - Kasidin, Sunarko; Karsono, Karsono (FOCUS: Jurnal of Law, 2021)
The purpose of this research is to find out the picture related to euthanasia that occurs and applies in Indonesia. What if, due to technological advances, there is "taking other people's lives" or "letting other people's lives be stolen by death. This research uses normative legal analysis. The data collection method uses the snowball method to continuously dig from various sources, books, other related literature studies. The results of this study illustrate that 1) The perspective of the Criminal Code in Indonesia is that convicting a person is not only because he has committed an act that fulfills the elements. - only the elements of the formulation of offenses (criminal act, actus reus) but still have to be taken into consideration is the problem of whether or not the person concerned is accountable for his actions (criminal responsibility, men's rea), 2) As a philosophical basis regarding the prohibition of euthanasia states, all kinds of killings are against morals.